Small states, big problems : small solutions from big countries - Singh, Rup (2008)
Argues that developed countries and donor agencies may have to reconsider special and differential provisions within the WTO on a sustainable basis, because small states have little potential for development of manufacturing and export sectors to a level which can sustain global competition.